Selling today : partnering to create value - Manning, Gerald L.; Ahearne, Michael; Reece, Barry L.; Goyal, Anita, 1972- (Harlow : Pearson, 2014)
This text helps students understand the value of developing their personal selling skills by exposing them to a careful integration of personal selling academic theory and real-world applications. And with the largest number of learn by doing materials available in any personal selling text, this book offers instructors a variety of teaching tools to strengthen the learning process. As the developed nations of the world transition from a production focus to a sales-and-service focus, this cutting-edge new edition prepares students to succeed as members of a new generation of businesspeople.
Previous edition: 2012.
Includes bibliographical references (pages 517-533) and indexes.
Keywords: Selling -- Study and teaching; Sales